2014
DOI: 10.3389/fnhum.2014.00493
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional relevance in face processing: happy faces of future interaction partners enhance the late positive potential

Abstract: Human face perception is modulated by both emotional valence and social relevance, but their interaction has rarely been examined. Event-related brain potentials (ERP) to happy, neutral, and angry facial expressions with different degrees of social relevance were recorded. To implement a social anticipation task, relevance was manipulated by presenting faces of two specific actors as future interaction partners (socially relevant), whereas two other face actors remained non-relevant. In a further control task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 80 publications
9
79
3
Order By: Relevance
“…refs 36, 41 and 44, we found no differences between emotional and neutral expressions on this component. In general, during passive viewing, emotion effects are smaller for faces compared to complex scenes and participants typically report less subjective arousal for faces49.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…refs 36, 41 and 44, we found no differences between emotional and neutral expressions on this component. In general, during passive viewing, emotion effects are smaller for faces compared to complex scenes and participants typically report less subjective arousal for faces49.…”
Section: Discussioncontrasting
confidence: 63%
“…For the LPP time windows a large parietal cluster was investigated (twenty-six electrodes: CCPz, CP5, CP5h, CP3, CP1, CPz, CP2, CP4, CP6, CPP5h, CPP3, CPPz, CPP4, P3, P1, Pz, P2, P4, PPO3, PPO1, PPOz, PPO2, PPO4, PO3, POz, PO4). Results did not change qualitatively, when selecting different literature-based electrode clusters for the N170, EPN or LPP343654.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent research has shown evidence that the N170 amplitude is also modulated by facial expression, being enhanced by positive or negative emotional faces (e.g., Calvo & Beltrán, 2013;Bublatzky, Gerdes, White, Riemer, & Alpers, 2014; see Rellecke et al, 2013, for a recent review of emotion effect on the N170). In addition, the modulation of the N170 amplitude by facial expression was influenced by the racial relationship between an onlooker and perceived faces (Tortosa, Lupiáñez, & Ruz, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, enhanced amplitudes have also been found, when faces were high in social relevance (e.g. romantic partner, family members; famous persons with negative or positive biography; Abdel Rahman, 2011;Guerra et al, 2012;Bublatzky et al, 2014;Tiedt et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 90%